Biocoversion of oil palm empty fruit bunch by Aspergillus niger EB4 under solid-state fermentation - Samsu Baharuddin, Azhari; Abd Razak, Nor Asma; Abdul Rahman, Nor'aini; Budiatman, Satiawihardja; Shirai, Yoshihito; Hassan, Mohd Ali (Universiti Putra Malaysia Press, 2009)
Oil palm empty fruit bunch (OPEFB) is an abundant lignocellulosic waste material generated from the palm oil industry. In this study, a locally isolated strain Aspergillus niger EB4 was cultivated on a pre-treated OPEFB as substrate to produce cellulase in the solid-state fermentation (SSF) process. The cellulase recovered was then subjected to a saccharification process. The strain was grown on the pre-treated OPEFB in a 250 ml Erlenmeyer flask and a 192 L tray cabinet bioreactor, at 80% moisture content and incubated for nine days under a static condition. The activities of the crude cellulase extract in the tray bioreactor were 19.02 ± 0.85, 6.36 ± 0.38 and 4.56 ± 0.26 U/g for β-glucosidase, CMCase and FPase, respectively on day 6 of fermentation. These results were similar to the results obtained from the flask experiment. The results demonstrated the feasibility of solid substrate fermentation of the OPEFB in both flask and tray cabinet bioreactor for the cellulase production. The enzymatic hydrolysis of OPEFB at 5% (w/v) was performed by utilizing the partially purified and crude cellulase incubated at 40°C for seven days. The partially purified cellullases hydrolyzed the pre-treated OPEFB and released 7.7 g/l of reducing sugar which corresponded to a 15% conversion.